Our souls at night - Haruf, Kent (Alfred A. Knopf, 2015)
In Holt, Colorado, widower Louis Waters is initially thrown when the widowed Addie Moore suggests that they spend time together, in bed, to stave off loneliness, but soon they are exchanging the confidences and memories.